If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -6 = 5.46 Reorder the terms: -6 + x = 5.46 Solving -6 + x = 5.46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 5.46 + 6 Combine like terms: -6 + 6 = 0 0 + x = 5.46 + 6 x = 5.46 + 6 Combine like terms: 5.46 + 6 = 11.46 x = 11.46 Simplifying x = 11.46
| 2(16+2x)=30 | | 15-3x=2x-3 | | 3(3.6667+-1)=8 | | 0.36g=1.8 | | 16-2g=26 | | a=(9-7)(9-4a) | | 2.4f=21.6 | | 22b=176 | | 13-2x=12x-13 | | 3(3.666+-1)=8 | | -7d=-84 | | -5(-16x-15)=-8(11+6x) | | y+21=34 | | -8+u=3 | | 3x+62=90+5x | | 67x-3=-3+67x | | 27.5+2= | | 8-3x=2x-3 | | 4x^2-7x+5=-2x+4 | | n-2+1=15 | | 63x+28=-26+63x | | 46x^2+50x-12.5=0 | | 3w+6=36-6 | | 3(n-1)=12 | | .2b=16 | | x*2+46=5*x-11 | | -6x-8+8x=-7x+4 | | 75=x*2.51x | | 2(3x-5)=7x+1 | | 1x+8y=38.5 | | 5x+6-2x=-6+x | | x^2-9x-41=-3x-1 |